Enhancing Student Learning Efficiency Through Project Oriented Problem Based Learning in Renewable Energy Technology Course - Pulluri, Harish; Naveen Kumar, A.; Saritha, P.; Reddy, Poli Lokeshwara (Journal of Engineering Education Transformations, 2025)
This paper investigates the transformation of a Renewable Energy Technology (RET) course syllabus via Project Oriented Problem Based Learning (POPBL), aligned with Constructive Alignment principles, to foster a student-centric learning environment. Traditional lecture-based methods often fall short in engaging students in complex subjects like renewable energy, prompting a shift towards PBL, emphasizing active learning and real-world problem-solving. The redesigning of the course involves mapping course objectives and core concepts to project themes and assignments, ensuring alignment between learning outcomes, assessments, and student activities. Integration of simulation models into project development offers hands-on experience in designing of the RET course. Post-implementation observations indicate that this approach significantly enhances problem-solving skills and fosters a deeper understanding of the subject matter, evidenced by the development of simulation-based projects. Therefore, the redesigning course syllabus empowers students to explore and apply renewable energy concepts practically, preparing them for future careers in the field and promoting innovation in renewable energy education.